(untitled) (Diametros, 2009)
Disputes concerning bioethics have become a special area of confrontation between theology and the empirical sciences. The characteristic features of theological reflection in the area of bioethics are the categories of being a creature, gift, and sacrifice. In theology life is understood as a fundamental value that cannot be understood by means of the category of property, but of gift and obligation. The exceptional value of the person with its corporeal-spiritual structure is also the normative basis for evaluating medical activities and omissions. An especially important element is the issue of adequate anthropology. In the face of reductionist tendencies theology underlines the importance of human corporeality, which cannot be reduced to its biological aspect. The issue of the immediate and long-term effects of activity and omission is also essential in searching for solutions in situations of conflict. Critical theological reflection will evaluate attempts to formulate explanations that are complete and final (and therefore necessarily concerned with world views) exclusively on the basis of empirical data.